Conservation psychology strategies for collaborative planning and impact evaluation. Issue 5 (12th April 2022) - Maynard, Lily; Howorth, Paige; Daniels, Jaret; Bunney, Katie‐Lyn; Snyder, Rebecca; Jenike, David; Barnhart, Trent; Spevak, Edward; Fitzgerald, Patrick; Gezon, Zak
Abstract: Conservation psychology principles can be useful for aligning organizations and scaling up conservation programs to increase impact while strategically engaging partners and communities. We can use findings and recommendations from conservation psychology to inform organizational collaborations between zoos and aquariums to maximize efficiency and coordination. In this study, we developed and evaluated a collaborative conservation initiative for monarch butterflies built with conservation psychology principles. We present our process for collaborative program planning and the resultant collective conservation plan as well as our formative evaluation findings after 1‐year of collaboration. We share best practices for group facilitation and conservation planning along with our evaluation instruments to support future collaborative conservation initiatives. Research highlights: The Saving Animals From Extinction Monarch Program facilitated stakeholder engagement and applied behavior change techniques to develop a collaborative plan for monarch conservation. This evaluation provides insights and tools to promote buy‐in and impact. Abstract : A monarch butterfly tagged by the conservation team at Oklahoma City Zoo and Botanical Garden as a part of their participation in the Association of Zoos and Aquariums Saving Animals From Extinction North American Monarch Program.